Risk Factors for Acute Respiratory Infections in Coastal Areas: A Literature Review and Bibliometric Analysis - Wa Ode Ratnasari; Sri Ratna Ningsih; Nur Juliana (Journal of Health Science and Pharmacy, 2025)
Background: Acute respiratory infections (ARIs) are a leading cause of morbidity and mortality among toddlers worldwide, particularly in developing countries. Coastal areas often experience specific public health challenges, including air pollution, overcrowding, and inadequate sanitation, all of which contribute to an increased incidence of ARIs in children. Objective: This study aims to analyze the risk factors influencing the incidence of acute respiratory infections in coastal areas. Methods: A systematic review was conducted following the PRISMA guidelines, combined with bibliometric analysis using VOSviewer. Results: From an initial 82 articles identified, 11 met the inclusion criteria. The analysis revealed that factors such as inadequate ventilation, high humidity, household smoking, and high population density were significantly associated with the incidence of ARIs in toddlers. Conclusion: Environmental interventions, including the improvement of household ventilation and public education on the hazards of indoor smoking, should be prioritized to reduce the risk of ARIs. Further research is warranted to assess the effectiveness of evidence-based interventions in addressing these health issues in coastal communities. Keywords: acute respiratory infection, coastal area, toddlers, ventilation, smoking